2004
DOI: 10.1128/jcm.42.1.311-319.2004
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes, Virulence Genes, and Intimin Types of Shiga Toxin (Verotoxin)-Producing Escherichia coli Isolates from Human Patients: Prevalence in Lugo, Spain, from 1992 through 1999

Abstract: We have analyzed the prevalence of Shiga toxin-producing Escherichia coli (STEC) in stool specimens of patients with diarrhea or other gastrointestinal alterations from the Xeral-Calde Hospital of Lugo City (Spain). STEC strains were detected in 126 (2.5%) of 5,054 cases investigated, with a progressive increase in the incidence from 0% in 1992 to 4.4% in 1999. STEC O157:H7 was isolated in 24 cases (0.5%), whereas non-O157 STEC strains were isolated from 87 patients (1.7%). STEC strains were (after Salmonella … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
158
5
7

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 200 publications
(183 citation statements)
references
References 45 publications
13
158
5
7
Order By: Relevance
“…Failure to isolate the STEC non-O157 from PCR positive stool samples is still a common problem encountered by researchers around the world (Blanco et al, 2004). According to previous studies, the non-isolation of viable STEC from PCR-positive samples might be due to the presence of very low numbers of bacteria (Khan et al, 2002), the presence of free stx phages in the sample (Karmali et al, 1985b) and loss of stx genes upon subcultivation of strains (Karch et al, 1992).…”
Section: Prevalence Of Stecmentioning
confidence: 99%
“…Failure to isolate the STEC non-O157 from PCR positive stool samples is still a common problem encountered by researchers around the world (Blanco et al, 2004). According to previous studies, the non-isolation of viable STEC from PCR-positive samples might be due to the presence of very low numbers of bacteria (Khan et al, 2002), the presence of free stx phages in the sample (Karmali et al, 1985b) and loss of stx genes upon subcultivation of strains (Karch et al, 1992).…”
Section: Prevalence Of Stecmentioning
confidence: 99%
“…The total value of Enterobacteriaceae was between 2.1 and 3.3 log cfu/cm 2 , with an average of 2.98 log cfu/ cm 2 . Different results have been obtained by Algino et al (2009), in small slaughterhouses from the US, where the values for TVC and Enterobacteriaceae were below the 1.0 log cfu/ cm 2 .…”
Section: Resultsmentioning
confidence: 99%
“…1 and 2 it can be noticed that none of the examined samples exceeded the maximum limit allowed of 5.0 log cfu / cm 2 4. From their analysis, it was observed that the results for samples examined in 2015 show have an average value for Enterobacteriaceae count was from 0.87 ± 0.1 log cfu / cm 2 in January and a maximum of 3.52 ± 0.06 log cfu / cm 2 in July (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Boerlin et al (1999) stated that adherence might be a more important factor in STEC-associated disease than Shiga toxins. However, it has been suggested that the eaeA-negative STEC strains may express additional adherence factors that allow them to colonize the intestinal tract (Paton and Paton, 2002;Blanco et al, 2004;Zweifel et al, 2005). Kudva et al (1997) reported that some ovine sorbitol-negative E. coli O157 isolates that were tested negative for the toxin and eae genes were positive for the K99 and F107 gene loci and all of non-O157 STEC isolates were positive for eaeA and both the K99 and F107 gene loci.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of STEC O157 strains was 62.5% and they were regarded as potential human pathogens, indicating that healthy sheep may serve as a reservoir of human pathogens (Beutin et al, 1993;Kudva et al, 1996;Kudva et al, 1997;Heuvelink et al, 1998). Intimin together with these phage-encoded toxins is considered essential for EHEC virulence in humans (Karmali et al, 1985;Ryan et al, 1986;Carter et al, 1987;Salmon et al, 1989;Paton and Paton, 1998;Boerlin et al, 1999;Blanco et al, 2004). The outer membrane protein, intimin, encoded by eaeA gene, has been shown to be necessary for the A/E activity of EHEC O157 (Jerse et al, 1990;Paton and Paton, 1998;Schmidt et al, 2001).…”
Section: Discussionmentioning
confidence: 99%